Qualitative and quantitative analysis of natural colorants from banana bracts - Fatihah Hayati, Abdul Sani (2010)
Natural colorants are preferable nowadays due to their beneficial health values. Natural colorants have been used as one of the colorants in food. The banana bracts, scientifically known as Musa X paradisiaca will be used in this study as the raw material. This study aimed on determining the best concentration of methanol in methanol-water, the best temperature to maintain the colorants in the samples extracted and the best storage condition. The banana bract layers will be washed and cut into smaller pieces. The colorant contains in banana bracts, known as anthocyanins will be extracted by blending 10g of banana bracts into the solvent until the bracts fully blended in a blender. Then, the sample extracted will be filtered to remove the residue of banana bract layers. Rotary evaporator were used to remove all methanol from the solutions extracted. Every sample was stored for 3, 6, 9, 12 and 15 days in a dark place. The characteristics of colorants were analyzed by using UV-Vis spectrophotometer. Qualitative analysis was based on the ability of the colorants to stands for 15 days. From the analysis, the best concentration of methanol in methanol- water if the sample was stored in the light was 30% at the temperature of 70°C. When the sample was stored in the dark, the best concentration of methanol in methanol-water was 40% at the temperature of 50°C. Qualitatively, all the samples could last up to 15 days.